Variações climáticas na precipitação do Rio Grande do Sul no clima presente e futuro - Cera, Jossana Ceolin (2011)
This study presents the analysis of precipitation trends for the Southern region of Brazil, for three present climate periods with a comparison between precipitation data and data of the regional Model RegCM3 and an analysis of future climate tendency. The study also presents the pattern of precipitation variability which operates in the South region o f Brazil. Using the Principal Components Analysis for daily precipitation data filtered in 2/20 day band, 20/100 day band and interannual band, spatial and temporal fields were found which represent the maximum variance of certain variabilities and in these, the variability pattern of precipitation for each season. And with the standard deviation series it was possible to determine the quantity of dry and rainy events present in each variability pattern. The pattern were calculated in three periods: from 1981 to 2007 for the precipitation data by Dr. Liebmann, from 1982 to 2006 for the data of the RegCM3 Model and from 2070 to 2086 for the data of the Model for future climate, being the A2 the scenery for emission used for the last period (considered pessimist). Three variability pattern were found, they were denominated Modo Sul, Modo PR and Modo Niño.